High mobility materials for CMOS applications - Collaert, Nadine (Woodhead Publishing, 2018)
High Mobility Materials for CMOS Applications provides a comprehensive overview of recent developments in the field of (Si)Ge and III-V materials and their integration on Si. The book covers material growth and integration on Si, going all the way from device to circuit design. While the book's focus is on digital applications, a number of chapters also address the use of III-V for RF and analog applications, and in optoelectronics. With CMOS technology moving to the 10nm node and beyond, however, severe concerns with power dissipation and performance are arising, hence the need for this timely work on the advantages and challenges of the technology.
Keywords: Metal oxide semiconductors, Complementary.; elektronické knihy; electronic books